Phát hiện nghi vấn sai đề BDT thứ 2 phải là dấu < chứ nhỉ
$ab + bc + ca <= a^2 + b^2 + c^2$
$<=> 2(ab + bc + ca) <= 2(a^2 + b^2 + c^2)$
$<=> 2a^2 + 2b^2 + 2c^2 - 2ab -2bc - 2ca >= 0$
$<=> (a^2 - 2ab + b^2) + (b^2 - 2bc + c^2) + (c^2 - 2ca + a^2) >= 0$
$<=> (a - b)^2 + (b - c)^2 + (c - a)^2 >= 0$ (luôn đúng)
Ta có:
$ab + bc = (a + c)b > b^2$ (do $a + c > b$)
$ac + bc = (a + b)c > c^2$ (do $a + b > c$)
$ab + ac = (b + c)a > a^2$ (do $b + c > a$)
Suy ra $ab + bc + ac + bc + ab + ca > a^2 + b^2 + c^2$
Hay $2(ab + bc + ca) > a^2 + b^2 + c^2$
Vậy $ab + bc + ca <= a^2 + b^2 + c^2 < 2(ab + bc + ca)$